Respuesta :
Answer:
These two numbers are -1 and -6 respectively.
Step-by-step explanation:
Suppose first number is x and the second number is y.
Then according to question-
( x + y ) = -7 ..............................(i)
x × y = 6 ................................(ii)
As we know that-
[tex](x - y)^{2}[/tex] = [tex](x + y )^{2} - 4 x y[/tex] .......................(iii)
Now, Putting values of equation (i), (ii) in equation (iii)-
We get,
[tex]( x - y )^{2}[/tex] = [tex]( - 7 )^{2}[/tex] - 4 × 6
[tex]( x - y )^{2}[/tex] = 49 - 24
[tex]( x - y )^{2}[/tex] = 25
( x - y ) = [tex]\sqrt{25}[/tex]
( x - y ) = 5..........................(iv)
After adding equation (i) and (iv)-
( x + y ) = -7
( x - y ) = 5
2 x = -2
x = -2 /2
x = -1
Now put x = -1 in equation (i)-
We get,
y = -7 - x
y = -7 - (- 1)
y = - 7 + 1
y = -6
Hence the both numbers x and y are -1, -6 respectively.